OPTIMIZATION OF HYDROCHEMICAL PRECIPITATION PROCESSES FOR THE SELECTIVE RECOVERY OF HIGH-PURITY NICKEL (II) FROM METALLURGICAL TECHNOGENIC SOLUTIONS - Abdullayeva Nigina Abdulhakimovna,Mirzakhmedov Rustamjon Mirxamidovich,Abduqahharova Nilufar Ikrom q (International Journal of Literature and Language Studies, 2026)
This research focuses on the optimization of the hydrochemical precipitation process to selectively recover high-purity nickel (II) from complex multicomponent technogenic solutions generated at the "Almalyk MMC" JSC. Following the sequential extraction of copper and cobalt, the remaining nickel-bearing liquor was systematically treated using sodium hydrogen phosphate (Na2HPO4) in a controlled acetic acid (CH3COOH)buffer system. Experimental trials were conducted to evaluate the influence of pH, temperature, reaction kinetics, and stoichiometric reagent ratios on the crystallization efficiency of nickel phosphate (Ni3(PO4)2 The optimal process parameters were established at a pH range of 4.5–5.0, a temperature spectrum of 20–25°C, and a precipitation duration of 10–15 minutes, resulting in a distinct green crystalline matrix. The structural configuration, chemical purity, and crystalline phase variations of the recovered nickel precipitates were comprehensively validated using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), X-ray Diffraction (XRD), and Spectrolab M10 optical emission profiling. The developed hydrochemical framework offers a high-selectivity, low-energy, and environmentally sustainable technological pathway for the production of industrial-grade nickel salts from secondary metallurgical waste streams.Keywords: Nickel precipitation; Chemical technology; Hydrochemistry; Crystalline phase; ICP-OES; Waste valorization.